Prominent role of liver in elevated plasma palmitoleate levels in response to rosiglitazone in mice fed high-fat diet - Kuda, O; Stankova, B; Tvrzicka, E; Hensler, M; Jelenik, T; Rossmeisl, M; Flachs, P; Kopecky, J (Journal of physiology and pharmacology, 2009)
UNLABELLED: In humans, antidiabetics thiazolidinediones (TZDs) upregulate stearoyl-CoA desaturase 1 (SCD1) gene in adipose tissue and increase plasma levels of SCD1 product palmitoleate, known to enhance muscle insulin sensitivity. Involvement of other tissues in the beneficial effects of TZDs on plasma lipid profile is unclear. In our previous study in mice, in which lipogenesis was suppressed by corn oil-based high-fat (cHF) diet, TZD rosiglitazone induced hepatic Scd1 expression, while liver triacylglycerol content increased, VLDL-triacylglycerol production decreased and plasma lipid profile and whole-body glycemic control improved. Aim of this study was to characterise contribution of liver to changes of plasma lipid profile in response to a 8-week-treatment by rosiglitazone in the cHF diet-fed mice. Rosiglitazone (10 mg/kg diet) upregulated expression of Scd1 in various tissues, with a stronger effect in liver as compared with adipose tissue or skeletal muscle. Rosiglitazone increased content of monounsaturated fatty acids in liver, adipose tissue and plasma, with palmitoleate being the most up-regulated fatty acid. In the liver, enhancement of SCD1 activity and specific enrichment of cholesteryl esters and phosphatidyl cholines with palmitoleate and vaccenate was found, while strong correlations between changes of various liver lipid fractions and total plasma lipids were observed (r=0.74-0.88). Insulin-stimulated glycogen synthesis was increased by rosiglitazone, with a stronger effect in muscle than in liver. CONCLUSIONS: changes in plasma lipid profile favouring monounsaturated fatty acids, mainly palmitoleate, due to the upregulation of Scd1 and enhancement of SCD1 activity in the liver, could be involved in the insulin-sensitizing effects of TZDs.
Keywords: Liver; Animals; kosterní svaly; orgánová specificita; mastné kyseliny; Oleic Acids; Fatty Acids, Monounsaturated; játra; Adipose Tissue, White; Fatty Acids; Thiazolidinediones; Up-Regulation; dietní tuky; lipidy; kyseliny olejové; Corn Oil; stearyl-CoA-desaturasa; Mice; Hypoglycemic Agents; rosiglitazon; upregulace; Lipids; Muscle, Skeletal; glykemický clamp; Rosiglitazone; thiazolidindiony; myši; kukuřičný olej; hypoglykemika; Stearoyl-CoA Desaturase; Insulin Resistance; inzulinová rezistence; Organ Specificity; kyseliny mastné mononenasycené; Random Allocation; zvířata; bílá tuková tkáň; Glucose Clamp Technique; Glycogen; Dietary Fats; náhodné rozdělení; glykogen